2013
DOI: 10.1158/1055-9965.epi-13-0583
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Exercise on Urinary 6-Sulfatoxymelatonin and Catecholamines in Young Women Participating in a 16-Week Randomized Controlled Trial

Abstract: Background Women with breast cancer have decreased levels of melatonin or its metabolite in plasma and/or urine. Methods We measured serum melatonin, urinary 6-sulfatoxymelatonin, catecholamines and cortisol in 141 sedentary young female participants in a clinical trial comparing 150 min/wk aerobic exercise for 4 months to no-exercise controls. Demographics, health surveys, body composition, sleep quality, fitness levels, blood and urine samples were obtained at baseline and 16 weeks. Results There were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Results from observational studies are conflicting,(4) and a short-term exercise intervention had no effect on aMT6s. (5) Results from our study add to these findings and, when taken together, provide evidence suggesting that PA does not substantially influence melatonin levels in either the short- or long-term. While our results suggest possible sex-related difference in associations between aMT6s levels and metabolic hormones, and Ki67 staining, they should be interpreted cautiously as correlations were modest.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Results from observational studies are conflicting,(4) and a short-term exercise intervention had no effect on aMT6s. (5) Results from our study add to these findings and, when taken together, provide evidence suggesting that PA does not substantially influence melatonin levels in either the short- or long-term. While our results suggest possible sex-related difference in associations between aMT6s levels and metabolic hormones, and Ki67 staining, they should be interpreted cautiously as correlations were modest.…”
Section: Discussionsupporting
confidence: 75%
“…(4) In the only randomized controlled trial (RCT) to date, a 16-week exercise intervention in healthy women (18-30 years) had no effect. (5) To our knowledge, no studies have examined the effect of a long-term PA intervention. The primary aim was to determine the effect of a 12-month exercise intervention vs. control on the principal urinary metabolite of melatonin,6-sulphatoxymelatonin (aMT6s) levels in sedentary men and women.…”
Section: Introductionmentioning
confidence: 99%
“…Study characteristics are presented in Supplementary Methods and Material ( Supplementary Tables S2A–S2D ). There were nine RCTs that included premenopausal ( 24 37 ), 18 RCTs that included postmenopausal ( 38 – 56 ), and one that included perimenopausal ( 57 ) women. Sample sizes ranged from 18 to 391 in studies of premenopausal, and from 16 to 382 in studies of postmenopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…51 , 53 , 54 , 57 ), and cortisol ( n = 7; refs. 24 , 29 , 37 , 39 , 42 , 52 , 55 ). In studies of premenopausal women, steroid hormone levels were assessed in the follicular ( n = 5; refs.…”
Section: Resultsmentioning
confidence: 99%
“…Although the epidemiologic literature is inconsistent, there is accumulating evidence that physical activity can decrease levels of stress biomarkers, specifically cortisol (Arazi et al, 2013; Lai et al, 2017; Roberts et al, 2013; Sotos-Prieto et al, 2015; Zawadzki et al, 2015), across different healthy study populations (Hayes et al, 2015; Laugero et al, 2011; Vaamonde et al, 2012; von Kanel et al, 2017). Conversely, several studies of physical activity interventions did not have any effect on resting cortisol levels measured in urine, saliva or blood (Arikawa et al, 2013; Brumby et al, 2013; Grandys et al, 2009; Hiruntrakul et al, 2010; Prick et al, 2015; Vaczi et al, 2014; Vale et al, 2009). One physical activity intervention trial in postmenopausal women demonstrated beneficial statistically significant changes in tumour necrosis factor-alpha and the cortisol to dehydroepiandrosterone sulfate ratio, but no changes in cortisol (Izzicupo et al, 2013).…”
Section: Discussionmentioning
confidence: 91%